Christological Heterodoxy as a Threat to the Kerygma in the Theology of Father Raniero Cantalamessa - Zborowski, Michał (Teologia w Polsce, 2020)
Any attempt to reduce or disintegrate the Christological dogma is not without an impact on the basic message of the good news, the Kerygma, as well as on its soteriological implications. The theological challenge is to make every effort to proclaim the first message as the announcement of the fullness of the revealed truth, but also to indicate the dangers arising from incomplete or unorthodox proclamation. The article presents negative consequences of heterodox Christological tendencies for the reality of the Kerygma in theology of Father Raniero Cantalamessa. These dogmatic threats and their consequences focus on the person of Jesus Christ and the mysteries of His death and resurrection.